Integrasi Nilai-Nilai Pendidikan Islam dan Pancasila Dalam Pembentukan Karakter Kewarganegaraan Siswa - Ana Amelia; Syamzaimar (Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to analyze the integration of Islamic educational values and Pancasila values in shaping students’ civic character amid the challenges of globalization that increasingly affect the morality and behavior of the younger generation. Islamic education plays an important role in instilling moral and spiritual values, while Pancasila serves as the foundation for national identity and citizenship values. The integration of these two value systems is expected to create students who possess strong religious principles, social responsibility, and national awareness. This research employed a qualitative approach using a library research method. Data were collected through the analysis of various relevant scientific sources, including books, academic journals, research articles, and previous studies related to Islamic education, Pancasila, character education, and civic education. The collected data were analyzed descriptively in order to obtain a comprehensive understanding of the research topic and identify the relationship between religious values and national values in students’ character development. The findings of this study indicate that Islamic educational values and Pancasila values share several common principles, such as honesty, responsibility, tolerance, justice, discipline, and mutual respect. The integration of these values can be implemented through classroom learning, teacher role modeling, habituation activities, and the creation of a supportive educational environment. However, several challenges remain, including limited curriculum integration, social environmental influences, and technological developments affecting students’ character formation. In conclusion, the integration of Islamic educational values and Pancasila values plays an important role in developing religious, responsible, and nationally minded students within modern educational environments today.